Provision of Psychosocial Care for Cancer Patients - Kathleen Abrahamson PhD, RN; Morgan Durham MHA; Kelli Norton BS; Bradley N. Doebbeling MD, MSc; Caroline Carney Doebbeling MD; James G. Anderson PhD (SAGE Publishing, 2011)
Although common, psychosocial distress is frequently under diagnosed and untreated in the US health care system. Previous research shows that cancer patients have unmet psychosocial needs, and provision of psychosocial care frequently falls to primary care providers who may lack the resources to adequately deal with complex psychosocial issues. We conducted 25 in-depth key informant interviews with health care professionals working within medical facilities that provide care to cancer patients. Cancer care centers included in the sample were located within both rural and urban communities in a midwestern state, and included providers of both inpatient and outpatient services. Interview questions addressed the assessment of psychosocial needs, availability of psychosocial care, perceptions of the effectiveness of psychosocial services, and perceptions of organizational processes to manage psychosocial needs among their patients. Respondents were also queried regarding recommendations for improving psychosocial care for patients with cancer. Assessment of psychosocial need in most settings was often subjective, not performed, or completed without access to an accepted standardized assessment tool, and clinical pathways to direct psychosocial care were often lacking. Because of the lack of systematic assessment, access to psychosocial care was frequently dependent on the subjective judgment of busy clinicians. This study shows the clear need for organizational and practice redesign initiatives in both rural and urban settings to improve the delivery of psychosocial services to cancer patients. A number of possible system improvements were identified, including the use of allied health providers, standardized screening, and information technology to increase the ease and efficiency of psychosocial assessment.